Punishing forest offenders: out of court or by the court? - Mohd, Rusli; Simin, Miskon (Universiti Putra Malaysia Press, 2009)
This study compared the extent of compounded and court cases and the penalties charged for the two categories of offences. Data on 119 offences, of which 73% were compounded cases covering the period 1998 to 2002, were analysed. It was found that the mean penalty charged per offence was higher for compounded cases (RM37,180) than court cases (RM26,988). The mean penalties for illegal logging, evasion of royalty and encroachment compounded cases were RM91, 690, RM27, 932 and RM147, 000, respectively. Meanwhile, the corresponding values for the court cases were RM39, 500, RM12 668 and RM47, 760, respectively. Further analysis revealed that there was no significant difference in the mean penalties between the three types of offences for the court cases. However, there were significant differences in mean penalties for the the compounded cases. In addition, the regression model developed showed that for every unit increase in the cubic meter of illegal logging, there was a corresponding increase in the penalty by RM4692.39 for the courts cases and RM3151.17 for the compounded cases. The results suggested that, in terms of deterrence, the courts are the better means for punishing forest offenders.